2011
DOI: 10.1002/mrc.2779
|View full text |Cite
|
Sign up to set email alerts
|

Geminal2J(29Si‐O‐29Si) couplings in oligosiloxanes and their relation to direct1J(29Si‐13C) couplings

Abstract: Absolute values of (79) geminal (2)J((29) Si-O-(29)Si) couplings were measured in an extensive series of (55) unstrained siloxanes dissolved in chloroform-d. Signs of (2)J((29)Si-O-(29)Si) in some (9) silicon hydrides were determined relative to (1)J((29)Si-(1)H) which are known to be negative. It is supposed that positive sign of the (2)J((29)Si-O-(29)Si) coupling found in all studied hydrides is common to all siloxanes. Theoretical calculations for simple model compounds failed to reproduce this sign and so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 76 publications
3
16
0
Order By: Relevance
“…[15] Scheme 7. [72] This research will surely be useful in the analysis of siloxane compounds that have more complex structures and could not be analyzed to date. [24,68] through siloxane bonding.…”
Section: Synthesis Of Explicit Siloxane Compounds With Suppressed Sidmentioning
confidence: 99%
“…[15] Scheme 7. [72] This research will surely be useful in the analysis of siloxane compounds that have more complex structures and could not be analyzed to date. [24,68] through siloxane bonding.…”
Section: Synthesis Of Explicit Siloxane Compounds With Suppressed Sidmentioning
confidence: 99%
“…The M( 13 C)‐M( 13 C) is doubly symmetrically 13 C (99 atom%) labeled 13 CH 3 (CH 3 ) 2 Si‐O‐Si(CH 3 ) 2 13 CH 3 sample. Preparation of these compounds was described elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…The only exception is R = H, where for the molecular fragment 1 H‐ 29 Si‐O‐ 29 Si, the couplings are 1 J (Si,H) ~ 200 Hz and 3 J (Si‐O‐Si‐H) ~ 1 Hz. All this appears to be the key reason why signs of 2 J (Si‐O‐Si) couplings in siloxanes were published only very recently, the sign detection being partly because of the E.COSY‐type experiment on fragments with direct Si‐H bond and partly by the method published in this article.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be seen that the Si peaks from Si(CH 3 ) 3 Si NMR spectra of dPDMSPEG and P(Si-g-dPDMSPEGA), as shown in Figure 2(c). 39,40 It is suggested that the expected product was synthesized and no unreacted Si H or generated Si OH. The peak at 6.8 ppm (peak a) was assigned to the terminals silicone of each repeating units.…”
Section: Synthesis and Characterization Of P(si-g-dpdmspega)mentioning
confidence: 99%